Religion education, intercultural education and human rights: A contribution for Cornelia Roux - Robert Jackson (Journal for the Study of Religion)
In this article, I draw on my own experience as a researcher, writer on theory and pedagogy of religion education¹ and contributor to European policy documents. This provides a basis to discuss some issues pertinent to Cornelia Roux's personal and professional journey as a researcher in religion education and related fields, including intercultural education, human rights education and citizenship education. I refer to our meetings over the years, both in and beyond South Africa, especially in the context of the International Network for Interreligious and Intercultural Education, and to the development of Professor Roux's ideas on Religion in Education (RiE), Religion and Education (RaE). An attempt is then made to articulate a view on the question of liberalism in relation to human rights, which connects to a stance on intercultural education and to religion education and values education more widely. The position developed is consistent with the approach to empirical research developed by Professor Roux and her team. The article concludes by relating Cornelia Roux's personal journey to some of the themes considered above.